Anatomic tunnel placement can be achieved with a modification to transtibial technique in single bundle anterior cruciate ligament reconstruction: A cadaver study. - Joon Kyu Lee; Sahnghoon Lee; Ki Tae Kim; Myung Chul Lee (PLoS ONE)
Placing the tunnels in the anatomic positions is important for successful restoration of knee function after anterior cruciate ligament reconstruction (ACLR). It has been shown that it is difficult to place the tunnels in the anatomic position using the transtibial technique. The purpose of this study was to evaluate the effect of each step of our modified transtibial technique (mTT) on the positioning of the femoral tunnel so as to assess whether the mTT could achieve anatomic placements of the tunnels without tibial tunnel expansion. Ten fresh-frozen cadaveric knees were used. First, the tibial tunnel was created in the center of ACL footprint. Then, a pin was inserted through the tibial tunnel using a femoral guide by four stepwise techniques: transtibial technique, additional anterior drawer force applied to the proximal tibia, another additional varus force applied to the tibia and finally, additional external rotation of the tibia and the femoral guide (mTT). Then, tibial tunnel was re-reamed using mTT with 10mm-diameter reamer. The pin positions in each technique on the femur were evaluated by the quadrant method and shapes of the tibial tunnel apertures were evaluated. Femoral pin positions in the four techniques were 23.6±4.5%, 28.4±3.4%, 30.1±3.8%, 33.2±4.5% in the superior-inferior position, and 23.9±4.3%, 26.2±3.7%, 32.0±4.3%, 36.9±4.8% in the anterior-posterior position, respectively. Pin position shifted to more inferior and posterior position with each step of mTT (all p values comparing superior-inferior and anterior-posterior positions of each step with positions of previous step were 0.008 or less). Using mTT, tibial tunnel aperture was 10.5±0.3mm wide and 12.9±1.1mm long. In conclusion, anatomic placements of femoral tunnels in ACLR without excessive tibial tunnel expansion could be achieved using the mTT.